Synchronization of the business and financial cycle in Poland - Markowski, Łukasz (Ekonomia i Prawo. Economics and Law, 2025)
Motivation: Nowadays, financial factors increasingly determine the functioning of the real sector. The assessment of the synchronization and interdependence of fluctuations in business and financial activity can be a kind of criterion for assessing the balance between the real and financial spheres. Aim: The aim of the research is to assess the degree of synchronization of the business and finan-cial cycle in Poland and the changes in the degree of this synchronization over time. Results: In the adopted research period, financial cyclical fluctuations of the dynamics of the stock market index and credit for the non-financial private sector did not clearly and unequivocal-ly determine cyclical fluctuations of the GDP growth rate in Poland. However, this does not mean that financial cycles in Poland are not related to the business cycle. The research re-sults indicate clear symptoms of dependence upon cyclical changes in the financial sphere and real economic activity. The degree of synchronization of the business and financial cycle in Poland is also variable over time.